Big Nate : on a roll - Peirce, Lincoln (New York : Harper, 2011)
Middle-schooler Nate Wright must compete with a new rival, the "perfect" Artur, for the grand prize of a customized skateboard in their scout troop contest.
School Library Journal, October 2011.
Kirkus Starred, July 2011.
Horn Book, September 2011.
2.9
3-6
440L
Keywords: Middle school students -- Juvenile fiction; Contests -- Juvenile fiction; Scouting (Youth activity) -- Juvenile fiction; Middle schools -- Juvenile fiction; Middle school students -- Fiction; Contests -- Fiction; Scouting (Youth activity) -- Fiction; Schools -- Fiction; Humorous stories; Cartoons and comics; Scouts and scouting -- Fiction; School stories; Humorous fiction; Comic books, strips, etc; Middle schools -- Fiction; Humorous fiction; Graphic novels